Clinical study evaluating the effectiveness and efficiency of Metrohex Plus Gel and diode laser therapy along with standard mechanical debridement for managing chronic periodontitis - Gaurav Singh; Shailendra S Chauhan; Aditya Sinha; Satendra Sharma (Wolters Kluwer Medknow Publications, 2022)
Aim: A study was carried out to determine how effective diode lasers and Metrohex Plus Gel are at managing chronic periodontitis when compared to standard periodontal therapy. Materials and Methods: A total of 90 sites having periodontal probing depth (PPD*) ≥5 mm were included with patients aged around 35-60 years. Each group contains 30 sites as follows: Group I - laser-assisted new attachment procedure*, Group II - Metrohex Plus Gel, Group III - scaling root planing (SRP)* alone. Results: Based on the average gingival index* value at baseline, 1 and 3 months, the values were 1.9 ± 0.67, 0.99 ± 0.26, and 0.89 ± 0.19, respectively. The mean plaque index* score decreased to 1.12 ± 0.31 at 1 month and 0.80 ± 0.31 at 3 months from 2.30 ± 0.58 at baseline. A PPD* reduction of 0.85 ± 0.03 mm was observed at 3 months for sites treated with laser, which was significantly higher than the reductions for sites treated with Metrohex plus (metronidazole 10 mg + chlorhexidine gluconate 0.25% w/w and hyaluronic acid) and SRP* alone. PPD* reductions were not significantly different between Groups I and II. Group II showed a 0.35 ± 0.11 mm improvement in clinical attachment levels compared to Group III. Conclusion: As opposed to simple SRP, diode laser therapy and Metrohex Plus Gel improve all clinical parameters in patients with periodontitis.